2022
DOI: 10.31186/jspi.id.17.1.29-43
|View full text |Cite
|
Sign up to set email alerts
|

Potential Benefits of Plant-Derived Products on Broiler Meat Characteristics - A Short Review

Abstract: Herbal supplements have been researched for decades as a safe alternative to synthetic antioxidants. These natural supplements may help broilers enhance their meat quality, growth, and physiological circumstances. The phenolic compounds in herbal products can serve as antioxidants, thereby responsible for lessening the negative effect of stress before slaughter. One of the most critical factors impacting broiler meats' physical, chemical, and oxidative stability is stress before slaughter. Reducing stress leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…In contrast, there was a significant difference in aroma between the two groups. Replenishment of natural feed additives during the rearing process may cause a change in the aroma of the carcass due to the components of the active compounds contained in natural feed additives entering the muscle tissue (Sugiharto 2022). In addition, there is a change in the fatty acid profile where fatty acids have a significant contribution to the aroma of a product (Song et al 2022).…”
Section: Organoleptic Analysismentioning
confidence: 99%
“…In contrast, there was a significant difference in aroma between the two groups. Replenishment of natural feed additives during the rearing process may cause a change in the aroma of the carcass due to the components of the active compounds contained in natural feed additives entering the muscle tissue (Sugiharto 2022). In addition, there is a change in the fatty acid profile where fatty acids have a significant contribution to the aroma of a product (Song et al 2022).…”
Section: Organoleptic Analysismentioning
confidence: 99%
“…In addition, the test was very subjective since it was associated with the sensation of the panelists when their teeth penetrated the meat and this could differ among the countries depending on their habits and acceptance (Suryati et al, 2018). According to Sugiharto (2022), the physical properties of broiler meats improved as a result of herbal supplementation.…”
Section: Consumer Acceptances Of Cooked Broiler Meatmentioning
confidence: 99%
“…In fact, there were contradictive results on the performances and yields of broilers fed the diet containing the moringa. This discrepancy could be subjected to the types of moringa plants, the kinds of birds and how they were raised, the levels of the inclusions, and the balances of the dietary compositions (Zulfan et al, 2021a;2022). They also reported that using a wild type of moringa combined with yellow corn in the diet caused a decline in broiler performances and carcass weight.…”
Section: Introductionmentioning
confidence: 99%
“…The fact that broiler chicken meat is less expensive than other animal protein sources, the business plays a crucial part in meeting the demand for animal protein. Despite its relatively lower prices, broiler chicken meat remains popular among consumers (Sugiharto, 2022).…”
Section: Introductionmentioning
confidence: 99%